Refractory concrete and preparation method thereof
Through the acylation reaction of modified basalt fibers and granite rock powder, combined with graphite additives, the existing refractory concrete has poor water resistance and poor corrosion resistance in high temperature environments, and has achieved better mechanical properties and thermal stability.
Patent Information
- Application Number
- CN202411854522.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing refractory concrete has poor water-resistance and poor corrosion resistance in high temperature environments, which affects its mechanical properties and thermal properties.
By treating modified basalt fibers and granite stone powder, the granite stone powder is grafted on the surface of basalt fibers by acylization reaction, and combined with graphite preparation additives to improve the dispersion and bonding properties of concrete.
The water-reflective properties, corrosion resistance and mechanical properties of refractory concrete are significantly improved, ensuring the volume stability and thermal stability of concrete.
Smart Images

Figure CN119306450B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to refractory concrete and a preparation method thereof. Background Art
[0002] Concrete is the most widely used man-made material in the world and also the most important material for building structures. With the rapid development of industry, buildings and equipment in high temperature, high pressure and high corrosion environments are becoming more and more common, which puts forward new requirements for concrete, especially fire resistance.
[0003] Refractory concrete is an amorphous refractory material that is prepared by adding water or other liquids to refractory aggregates, powders and binders and used directly without calcination. It is also called refractory pouring material. Refractory concrete is an unburned product with a simple production process, energy saving, and is suitable for mechanized construction. It is mainly used in industrial kilns such as metallurgy, petroleum, chemical industry, building materials, and machinery.
[0004] Under the high temperature of fire, changes in various properties of concrete materials cause stress redistribution inside components and structures, thereby reducing the performance of structural components and endangering the safety of the overall structure. Under fire, as the temperature rises, the material composition in the concrete will change due to high temperature reactions, which directly affects the mechanical and thermal properties of the concrete. Therefore, refractory concrete should not only have good fire resistance but also good mechanical properties.
[0005] Chinese patent CN109665782A discloses a fiber composite concrete with high fire resistance and a preparation method thereof, specifically disclosing that the concrete includes silicate cement, natural oil stone, gelatin fiber, fatty acyl citrate, modified polycaprolactone fiber, sodium methylsiliconate, polyoxyalkylene alkyl ether sulfate, acrylic acid-acrylate copolymer, sodium tripolyphosphate, citric acid-chitosan, ethylene bisstearamide, calcium carbonate whisker, vinyl acetate, vinyl polysiloxane, silica powder, methacrylic acid, hexadecyltrimethylammonium bromide, ammonium persulfate, manganese carbide, quartz glass powder, and nano-titanium oxide water repellent ingredients; the patent mainly improves the fire resistance of concrete by controlling the amount of fiber added and modifying the fiber, and at the same time, mixes with other acid esters and water repellents, and combines with natural oil stone and other ingredients to make the concrete stress concentrated and dispersed evenly to avoid concrete cracking; however, the refractory concrete prepared by the patent has poor water seepage resistance and poor corrosion resistance.
[0006] Therefore, it is urgent to develop a kind of refractory concrete and preparation method thereof. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a refractory concrete and a preparation method thereof. The concrete has good refractory performance, good mechanical properties, excellent water seepage resistance and excellent corrosion resistance.
[0008] In view of the above technical problems, the present invention adopts the following technical solutions:
[0009] A method for preparing refractory concrete includes the steps of modified basalt fiber, modified granite powder, grafting and mixing, which are specifically as follows:
[0010] 1. Modified basalt fiber
[0011] (1) Preprocessing
[0012] The basalt fiber is placed in a plasma device for plasma treatment, the vacuum degree is controlled to be 2.8-3.2 Pa, the treatment temperature is 166-173° C., the treatment time is 6.3-6.7 min, and the treatment power is 324-332 W. After the treatment, the fiber is placed in an ethanol solution, polyethylene glycol stearate and polyethylene glycol monolaurate are added, the temperature is increased to 53-60° C. at a rate of 0.6-1.0° C. / min, stirred for 28-32 min, filtered and dried, and the pretreated basalt fiber is obtained.
[0013] The basalt fiber has a length of 1.0-1.4 mm and a diameter of 3.8-4.2 μm;
[0014] The mass concentration of the ethanol solution is 33-37%;
[0015] The mass ratio of the basalt fiber, the ethanol solution, the polyethylene glycol stearate, and the polyethylene glycol monolaurate is 9.5-10.4:85-90:1.0-1.4:0.8-1.2;
[0016] (2) Carboxylation
[0017] The pretreated basalt fiber is placed in an ethanol solution, stirred evenly, and then a carboxylating agent is added for ultrasonic treatment, wherein the ultrasonic time is 18-23 minutes, the ultrasonic power is 110-120 W, the ultrasonic frequency is 23-28 kHz, and the ultrasonic temperature is 40-44° C. After the ultrasonic treatment, a precooling treatment is performed, wherein the precooling time is 9.8-10.3 hours, and the precooling temperature is -26 to -22° C. After the precooling, a freezing treatment is performed, wherein the freezing time is 22-24 hours, and the precooling temperature is -43 to -36° C. After the precooling, a modified basalt fiber is obtained;
[0018] The mass concentration of the ethanol solution is 34-36%;
[0019] The mass ratio of the pretreated basalt fiber, the ethanol solution, and the carboxylating agent is 7.4-8.0:90-96:1.4-1.7;
[0020] The carboxylating agent is a mixture of citric acid and salicylic acid, and the mass ratio of the citric acid to the salicylic acid is 1.1-1.3:1.4-1.6.
[0021] 2. Modified granite powder
[0022] Put granite powder in an ethanol solution, add sorbitol dodecanoate and polyoxyethylene sorbitan monolaurate and stir at a temperature of 46-50°C. After stirring evenly, add threonine and perform ball milling. The ball milling time is 26-30 minutes, the ball milling speed is 114-125 rpm, and the ball-to-material ratio is 3-5:1. After the ball milling is completed, filter and dry to obtain modified granite powder.
[0023] The particle size of the granite powder is 135-145nm;
[0024] The mass concentration of the ethanol solution is 45-50%;
[0025] The mass ratio of the granite powder, ethanol solution, sorbitan laurate, polyoxyethylene sorbitan monolaurate and threonine is 8.3-8.7:90-97:1.0-1.2:1.1-1.5:4.5-4.9.
[0026] 3. Grafting
[0027] Add modified basalt fiber to N,N-dimethylformamide, stir evenly, then add N,N-carbonyldiimidazole, introduce nitrogen, heat to 56-60°C, stir and react for 3.0-3.5h, add modified granite powder after the reaction, heat to 85-88°C at a rate of 1.8-2.2°C / min, stir and react again, the reaction time is 7.8-8.3h, wash and dry after the reaction, and obtain granite powder coated basalt fiber;
[0028] The mass ratio of the N,N-dimethylformamide, modified basalt fiber, N,N-carbonyldiimidazole and modified granite powder is 1760-1830:4.1-4.4:0.16-0.20:10.3-10.6.
[0029] 4. Mixing
[0030] Add granite crushed stone, P.O42.5 ordinary Portland cement, fly ash, granite powder coated basalt fiber, and calcium carbonate whisker to deionized water, stir at a stirring speed of 435-461 rpm, add polycarboxylic acid water reducer, additives, polyoxyethylene alkyl alcohol amine, and carboxymethyl cellulose and continue stirring at a stirring temperature of 83-87° C., stir evenly, cool to room temperature, and obtain refractory concrete;
[0031] The particle size of the granite crushed stone is 5.2-5.6 mm, and the bulk density is 1710-1716 kg / m 3 ;
[0032] The fly ash has a loss on ignition of ≤3.0%, a 45 μm sieve residue of ≤12%, and a moisture content of ≤1.0%;
[0033] The mass ratio of the deionized water, granite crushed stone, P.O42.5 ordinary Portland cement, fly ash, granite powder coated basalt fiber, calcium carbonate whisker, polycarboxylic acid water reducer, additive, polyoxyethylene alkyl alcohol amine, and carboxymethyl cellulose is 16-18:93-97:46-50:68-73:35-38:10-13:2.0-2.4:7.3-7.5:2.4-2.6:1.7-2.0;
[0034] The preparation method of the auxiliary agent is as follows: placing graphite in a 28-32wt% ethanol solution, heating to 53-57°C at a rate of 1.3-1.7°C / min, adding glycerol and paraffin, stirring evenly, adding gelatin for homogenization, the homogenization time is 4-6min, the homogenization pressure is 3.0-3.4MPa, and after the homogenization is completed, drying to obtain the auxiliary agent;
[0035] The particle size of the graphite is 95-110nm;
[0036] The mass ratio of the graphite, ethanol solution, glycerol, paraffin and gelatin is 11-13:45-50:0.6-0.8:1.3-1.5:1.1-1.3.
[0037] A refractory concrete is prepared by the above preparation method.
[0038] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0039] 1. In the present invention, basalt fiber is first pretreated, wherein the plasma treatment causes obvious etching on the surface of the basalt fiber, thereby increasing the specific surface area, and the surface activity of the basalt fiber is improved by combining with polyethylene glycol stearate and polyethylene glycol monolaurate components, thereby enhancing the dispersion performance, and then treated with a carboxylating agent, wherein the hydroxyl group of the carboxylating agent forms a hydrogen bond with the hydroxyl group of the pretreated basalt fiber, thereby making the surface of the basalt fiber contain a carboxyl group; then the granite powder is treated with threonine, wherein the hydroxyl group and carboxyl group of the threonine are bonded with the granite powder, thereby making the surface of the granite powder rich in amino groups, and then the modified basalt fiber is subjected to an acylation reaction with the modified granite powder, and the granite powder is grafted onto the surface of the basalt fiber through an amide bond, and the two It has strong binding force, uniform structure, good dispersion performance in the concrete system, good anti-permeability, stable properties, and ensures the volume stability of the concrete. Then, graphite is used to prepare the additive. Graphite has good anti-permeability, fire resistance and corrosion resistance. The propylene glycol mainly improves the dispersion performance and reduces agglomeration. Paraffin and gelatin can increase the adhesion inside the concrete after melting with the increase of temperature, and can also prevent the heat transfer inside the concrete. The prepared additive is evenly mixed with other ingredients, and graphite can be combined with the carboxyl, hydroxyl, amide groups, etc. of the granite powder-coated basalt fiber. It is evenly mixed with other ingredients. The prepared concrete has good homogeneity, stable properties, good anti-permeability, good fire resistance, excellent corrosion resistance, and strong volume thermal stability.
[0040] 2. The refractory concrete prepared by the present invention has a compressive strength of 75.9-77.8 MPa and a flexural strength of 13.0-13.7 MPa;
[0041] 3. The refractory concrete prepared in the present invention is immersed in a 30wt% sodium chloride solution for 24h, then immersed in a 30wt% sodium hydroxide solution for 24h, then dried at 110°C for 24h, and finally calcined at 400°C for 4h. The measured compressive strength is 71.3-74.2MPa and the flexural strength is 12.3-13.1MPa.
[0042] 4. The refractory concrete prepared in the present invention is immersed in a 30wt% sodium chloride solution for 24h, then immersed in a 30wt% sodium hydroxide solution for 24h, then dried at 110°C for 24h, and finally calcined at 800°C for 4h. The measured compressive strength is 69.9-72.5MPa and the flexural strength is 12.1-12.9MPa.
[0043] 5. The refractory concrete prepared by the present invention has good volume stability. The refractory concrete is dried at 110°C for 24 hours and then sintered at 1200°C. The measured linear shrinkage is 0.21-0.27%;
[0044] 6. The refractory concrete prepared by the present invention has good water seepage resistance, and the maximum hydrostatic pressure without water seepage is 0.95-1.04MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a process flow chart of the method for preparing refractory concrete in the present invention. DETAILED DESCRIPTION
[0046] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0047] Example 1: Figure 1 As shown, the present invention provides a method for preparing refractory concrete, wherein the preparation method includes the steps of modified basalt fiber, modified granite powder, grafting and mixing;
[0048] 1. Modified basalt fiber
[0049] (1) Preprocessing
[0050] 10g of basalt fiber was placed in a plasma device for plasma treatment, the vacuum degree was controlled to be 3.0Pa, the treatment temperature was 170℃, the treatment time was 6.5min, and the treatment power was 328W. After the treatment, it was placed in 87g of ethanol solution, 1.2g of polyethylene glycol stearate and 1.0g of polyethylene glycol monolaurate were added, the temperature was raised to 56℃ at a rate of 0.8℃ / min, stirred for 30min, filtered and dried, and the pretreated basalt fiber was obtained;
[0051] The basalt fiber has a length of 1.2 mm and a diameter of 4.0 μm;
[0052] The mass concentration of the ethanol solution is 35%;
[0053] (2) Carboxylation
[0054] 7.6 g of pretreated basalt fiber was placed in 92 g of ethanol solution, and after being stirred evenly, 1.6 g of carboxylating agent was added for ultrasonic treatment, the ultrasonic time was 20 min, the ultrasonic power was 115 W, the ultrasonic frequency was 26 kHz, and the ultrasonic temperature was 42 ° C. After the ultrasonic treatment, a precooling treatment was performed, the precooling time was 10 h, and the precooling temperature was -24 ° C. After the precooling, a freezing treatment was performed, the freezing time was 23 h, and the precooling temperature was -40 ° C. After the precooling, a modified basalt fiber was obtained;
[0055] The mass concentration of the ethanol solution is 35%;
[0056] The carboxylating agent is a mixture of citric acid and salicylic acid, and the mass ratio of the citric acid to the salicylic acid is 1.2:1.5.
[0057] 2. Modified granite powder
[0058] 8.5 g of granite powder was placed in 94 g of ethanol solution, 1.1 g of sorbitol dodecanoate and 1.3 g of polyoxyethylene sorbitan monolaurate were added and stirred at 48°C. After stirring evenly, 4.7 g of threonine was added and ball milled for 28 min at a ball milling speed of 120 rpm and a ball-to-material ratio of 4:1. After the ball milling was completed, the modified granite powder was obtained by filtration and drying.
[0059] The particle size of the granite powder is 140nm;
[0060] The mass concentration of the ethanol solution is 47%.
[0061] 3. Grafting
[0062] Add 4.3g of modified basalt fiber to 1800gN,N-dimethylformamide, stir evenly, add 0.18gN,N-carbonyldiimidazole, introduce nitrogen, heat to 58°C, stir and react for 3.2h. After the stirring reaction, add 10.4g of modified granite powder, heat to 87°C at a rate of 2.0°C / min, stir and react again, the reaction time is 8.0h. After the reaction, wash and dry to obtain granite powder-coated basalt fiber.
[0063] 4. Mixing
[0064] Add 95g of granite crushed stone, 47g of P.O42.5 ordinary Portland cement, 70g of fly ash, 36g of granite powder coated basalt fiber, and 12g of calcium carbonate whisker to 17g of deionized water, stir at a stirring speed of 450rpm, add 2.2g of polycarboxylate water reducer, 7.4g of additive, 2.5g of polyoxyethylene alkyl acylamine, and 1.8g of carboxymethyl cellulose and continue stirring at a stirring temperature of 85°C, stir evenly, and cool to room temperature to obtain refractory concrete;
[0065] The particle size of the granite crushed stone is 5.4 mm and the bulk density is 1713 kg / m 3 ;
[0066] The fly ash has a loss on ignition of ≤3.0%, a 45 μm sieve residue of ≤12%, and a moisture content of ≤1.0%;
[0067] The preparation method of the auxiliary agent is as follows: placing graphite in a 30wt% ethanol solution, heating to 55°C at a rate of 1.5°C / min, adding glycerol and paraffin, stirring evenly, adding gelatin for homogenization, the homogenization time is 5min, the homogenization pressure is 3.2MPa, and after the homogenization is completed, drying to obtain the auxiliary agent;
[0068] The particle size of the graphite is 100 nm;
[0069] The mass ratio of the graphite, ethanol solution, glycerol, paraffin and gelatin is 12:47:0.7:1.4:1.2.
[0070] Example 2: 1. Modified basalt fiber
[0071] (1) Preprocessing
[0072] 9.5 g of basalt fiber was placed in a plasma device for plasma treatment, and the vacuum degree was controlled to be 2.8 Pa, the treatment temperature was 166 ° C, the treatment time was 6.3 min, and the treatment power was 324 W. After the treatment, it was placed in 85 g of ethanol solution, 1.0 g of polyethylene glycol stearate and 0.8 g of polyethylene glycol monolaurate were added, and the temperature was raised to 53 ° C at a rate of 0.6 ° C / min, stirred for 28 min, filtered and dried, and the pretreated basalt fiber was obtained;
[0073] The basalt fiber has a length of 1.0 mm and a diameter of 3.8 μm;
[0074] The mass concentration of the ethanol solution is 33%;
[0075] (2) Carboxylation
[0076] 7.4 g of pretreated basalt fiber was placed in 90 g of ethanol solution, and after being stirred evenly, 1.4 g of carboxylating agent was added for ultrasonic treatment, the ultrasonic time was 18 min, the ultrasonic power was 110 W, the ultrasonic frequency was 23 kHz, and the ultrasonic temperature was 40 ° C. After the ultrasonic treatment, a precooling treatment was performed, the precooling time was 9.8 h, and the precooling temperature was -26 ° C. After the precooling, a freezing treatment was performed, the freezing time was 22 h, and the precooling temperature was -43 ° C. After the precooling, a modified basalt fiber was obtained;
[0077] The mass concentration of the ethanol solution is 34%;
[0078] The carboxylating agent is a mixture of citric acid and salicylic acid, and the mass ratio of the citric acid to the salicylic acid is 1.1:1.4.
[0079] 2. Modified granite powder
[0080] 8.3 g of granite powder was placed in 90 g of ethanol solution, 1.0 g of sorbitol dodecanoate and 1.1 g of polyoxyethylene sorbitan monolaurate were added and stirred at a stirring temperature of 46°C. After stirring evenly, 4.5 g of threonine was added and ball milled for 26 min at a ball milling speed of 114 rpm and a ball-to-material ratio of 3:1. After the ball milling was completed, the modified granite powder was obtained by filtration and drying.
[0081] The particle size of the granite powder is 135nm;
[0082] The mass concentration of the ethanol solution is 45%.
[0083] 3. Grafting
[0084] Add 4.1g of modified basalt fiber to 1760g of N,N-dimethylformamide, stir evenly, add 0.16g of N,N-carbonyldiimidazole, introduce nitrogen, heat to 56°C, stir and react for 3.0h. After the stirring reaction, add 10.3g of modified granite powder, heat to 85°C at a rate of 1.8°C / min, stir and react again, the reaction time is 7.8h. After the reaction, wash and dry to obtain granite powder-coated basalt fiber.
[0085] 4. Mixing
[0086] Add 93g of granite crushed stone, 46g of P.O42.5 ordinary Portland cement, 68g of fly ash, 35g of granite powder coated basalt fiber, and 10g of calcium carbonate whisker to 16g of deionized water, stir at a stirring speed of 435rpm, stir evenly, add 2.0g of polycarboxylate water reducer, 7.3g of additive, 2.4g of polyoxyethylene alkyl acyl alcohol amine, and 1.7g of carboxymethyl cellulose and continue stirring at a stirring temperature of 83°C. After stirring evenly, cool to room temperature to obtain refractory concrete;
[0087] The particle size of the granite crushed stone is 5.2 mm and the bulk density is 1710 kg / m 3 ;
[0088] The fly ash has a loss on ignition of ≤3.0%, a 45 μm sieve residue of ≤12%, and a moisture content of ≤1.0%;
[0089] The preparation method of the auxiliary agent is as follows: placing graphite in a 28wt% ethanol solution, heating it to 53°C at a rate of 1.3°C / min, adding glycerol and paraffin, stirring evenly, adding gelatin for homogenization, the homogenization time is 4 minutes, the homogenization pressure is 3.0MPa, and after the homogenization is completed, drying to obtain the auxiliary agent;
[0090] The particle size of the graphite is 95 nm;
[0091] The mass ratio of the graphite, ethanol solution, glycerol, paraffin and gelatin is 11:45:0.6:1.3:1.1.
[0092] Example 3: 1. Modified basalt fiber
[0093] (1) Preprocessing
[0094] 10.4 g of basalt fiber was placed in a plasma device for plasma treatment, the vacuum degree was controlled to be 3.2 Pa, the treatment temperature was 173 ° C, the treatment time was 6.7 min, and the treatment power was 332 W. After the treatment, it was placed in 90 g of ethanol solution, 1.4 g of polyethylene glycol stearate and 1.2 g of polyethylene glycol monolaurate were added, the temperature was raised to 60 ° C at a rate of 1.0 ° C / min, stirred for 32 min, filtered and dried, and the pretreated basalt fiber was obtained;
[0095] The basalt fiber has a length of 1.4 mm and a diameter of 4.2 μm;
[0096] The mass concentration of the ethanol solution is 37%;
[0097] (2) Carboxylation
[0098] 8.0g of pretreated basalt fiber was placed in 96g of ethanol solution, and after being stirred evenly, 1.7g of carboxylating agent was added for ultrasonic treatment, the ultrasonic time was 23min, the ultrasonic power was 120W, the ultrasonic frequency was 28kHz, and the ultrasonic temperature was 44°C. After the ultrasonic treatment, a precooling treatment was performed, the precooling time was 10.3h, and the precooling temperature was -22°C. After the precooling, a freezing treatment was performed, the freezing time was 24h, and the precooling temperature was -36°C. After the precooling, a modified basalt fiber was obtained;
[0099] The mass concentration of the ethanol solution is 36%;
[0100] The carboxylating agent is a mixture of citric acid and salicylic acid, and the mass ratio of the citric acid to the salicylic acid is 1.3:1.6.
[0101] 2. Modified granite powder
[0102] 8.7 g of granite powder was placed in 97 g of ethanol solution, 1.2 g of sorbitol dodecanoate and 1.5 g of polyoxyethylene sorbitan monolaurate were added and stirred at 50°C. After stirring evenly, 4.9 g of threonine was added and ball milled for 30 min at a ball milling speed of 125 rpm and a ball-to-material ratio of 5:1. After the ball milling was completed, the modified granite powder was obtained by filtration and drying.
[0103] The particle size of the granite powder is 145nm;
[0104] The mass concentration of the ethanol solution is 50%.
[0105] 3. Grafting
[0106] Add 4.4 g of modified basalt fiber to 1830 g of N, N-dimethylformamide, stir evenly, then add 0.20 g of N, N-carbonyldiimidazole, introduce nitrogen, heat to 60 ° C, stir and react for 3.5 hours. After the stirring reaction, add 10.6 g of modified granite powder, heat to 88 ° C at a rate of 2.2 ° C / min, stir and react again, the reaction time is 8.3 hours. After the reaction, wash and dry to obtain granite powder coated basalt fiber.
[0107] 4. Mixing
[0108] Add 97g of granite crushed stone, 50g of P.O42.5 ordinary Portland cement, 73g of fly ash, 38g of granite powder coated basalt fiber, and 13g of calcium carbonate whisker to 18g of deionized water, stir at a stirring speed of 461rpm, stir evenly, add 2.4g of polycarboxylate water reducer, 7.5g of additive, 2.6g of polyoxyethylene alkyl acyl alcohol amine, and 2.0g of carboxymethyl cellulose and continue stirring at a stirring temperature of 87°C. After stirring evenly, cool to room temperature to obtain refractory concrete;
[0109] The particle size of the granite crushed stone is 5.6 mm and the bulk density is 1716 kg / m 3 ;
[0110] The fly ash has a loss on ignition of ≤3.0%, a 45 μm sieve residue of ≤12%, and a moisture content of ≤1.0%;
[0111] The preparation method of the auxiliary agent is as follows: placing graphite in a 32wt% ethanol solution, heating to 57°C at a rate of 1.7°C / min, adding glycerol and paraffin, stirring evenly, adding gelatin for homogenization, the homogenization time is 6 minutes, the homogenization pressure is 3.4MPa, and after the homogenization is completed, drying to obtain the auxiliary agent;
[0112] The particle size of the graphite is 110 nm;
[0113] The mass ratio of the graphite, ethanol solution, glycerol, paraffin and gelatin is 13:50:0.8:1.5:1.3.
[0114] Comparative Example 1:
[0115] Based on Example 1, the changes are as follows:
[0116] In the step of modifying basalt fibers, the pretreatment step is omitted, and in the carboxylation step, an equal amount of pretreated basalt fibers is replaced by basalt fibers that have not been treated in any way;
[0117] The step of modifying granite powder is omitted;
[0118] The grafting step is to add 4.3g of modified basalt fiber to 1800g of N,N-dimethylformamide, heat it to 58°C, stir it for 3.2h, add 10.4g of granite powder after stirring, heat it to 87°C at a rate of 2.0°C / min, stir it again for 8.0h, wash and dry it, and obtain granite powder coated basalt fiber;
[0119] The rest of the operations are the same.
[0120] Comparative Example 2:
[0121] Based on Example 1, the changes are as follows:
[0122] In the step of modifying the granite powder, sorbitan laurate and polyoxyethylene sorbitan monolaurate are replaced by ethanol solution in equal amounts; the mass concentration of the ethanol solution is 47%;
[0123] In the mixing step, the additive is replaced by graphite in equal amount, and the particle size of the graphite is 100 nm;
[0124] The rest of the operations are the same.
[0125] Performance Testing
[0126] The concretes prepared in Examples 1-3 and Comparative Examples 1-2 were respectively made into cubic concrete specimens of 150 mm × 150 mm × 150 mm, and the concrete specimens were cured for 28 days to prepare concrete test specimens. The following performance tests were performed on the concrete test specimens:
[0127] 1. Strength
[0128] The concrete test specimens prepared in Examples 1-3 and Comparative Examples 1-2 were tested for compressive strength and flexural strength, and the test results are as follows:
[0129] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Compressive strength MPa 77.8 75.9 73.5 61.4 64.1 Flexural strength MPa 13.7 13.0 13.3 9.5 7.9
[0130] 2. High temperature corrosion resistance
[0131] The concrete test specimens prepared in Example 1-3 and Comparative Example 1-2 were first immersed in a 30wt% sodium chloride solution for 24h, then immersed in a 30wt% sodium hydroxide solution for 24h, then dried at 110°C for 24h, and finally calcined at 400°C and 800°C for 4h, respectively. After naturally returning to room temperature, the compressive strength and flexural strength were tested again. The test results are as follows:
[0132] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 400℃ compressive strength MPa 74.2 71.3 69.6 50.4 53.8 400℃ flexural strength MPa 13.1 12.3 12.6 7.9 6.7 800℃ compressive strength MPa 72.5 69.9 68.1 49.5 52.3 800℃ flexural strength MPa 12.9 12.1 12.4 7.7 6.5
[0133] 3. Shrinkage
[0134] The concrete test specimens prepared in Example 1-3 and Comparative Example 1-2 were first dried at 110°C for 24 hours, then sintered at 1200°C, and the linear shrinkage was tested. The test results are as follows:
[0135] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Linear shrinkage% 0.21 0.27 0.23 1.6 1.3
[0136] 4. Water-resistance
[0137] The concrete test specimens prepared in Examples 1-3 and Comparative Examples 1-2 were tested for the maximum hydrostatic pressure without water seepage, and the test results were as follows:
[0138] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Maximum hydrostatic pressure without water seepage MPa 1.04 0.95 0.99 0.70 0.81
[0139] The present invention pre-treats the basalt fiber first, wherein the plasma treatment causes obvious etching on the surface of the basalt fiber, increases the specific surface area, combines with polyethylene glycol stearate and polyethylene glycol monolaurate components, improves the surface activity of the basalt fiber, and enhances the dispersion performance, and then treats with a carboxylating agent, wherein the hydroxyl group of the carboxylating agent forms a hydrogen bond with the hydroxyl group of the pre-treated basalt fiber, so that the surface of the basalt fiber contains a carboxyl group; then, the granite powder is treated with threonine, and the hydroxyl group and carboxyl group of the threonine are bonded with the granite powder, so that the surface of the granite powder is rich in amino groups, and then the modified basalt fiber and the modified granite powder are subjected to an acylation reaction, and the granite powder is grafted on the surface of the basalt fiber through an amide bond, and the two are combined. The invention has strong strength, uniform structure, good dispersion performance in the concrete system, good anti-permeability, stable properties, and ensures the volume stability of the concrete. Then, graphite is used to prepare the additive. Graphite has good anti-permeability, fire resistance and corrosion resistance. The propylene glycol mainly improves the dispersion performance and reduces agglomeration. Paraffin and gelatin can increase the adhesion inside the concrete after melting as the temperature rises, and can also prevent the heat transfer inside the concrete. The prepared additive is evenly mixed with other ingredients, and graphite can be combined with the carboxyl, hydroxyl and amide groups of the granite powder-coated basalt fiber. It is evenly mixed with other ingredients. The prepared concrete has good homogeneity, stable properties, good anti-permeability, good fire resistance, excellent corrosion resistance and strong volume thermal stability.
[0140] Comparative Example 1 omits the pretreatment step of basalt fiber. In the carboxylation step, the basalt fiber has poor dispersion and serious aggregation. Comparative Example 1 omits the modification step of granite powder. It is directly mixed with modified basalt fiber, has weak and unstable binding force, poor dispersion in the concrete system, and poor compatibility with other components, which leads to poor homogeneity, low strength, poor stability, and poor water seepage resistance of concrete.
[0141] Comparative Example 2 omits the sorbitan dodecanoate and polyoxyethylene sorbitan monolaurate components in the granite powder, resulting in poor binding of the granite powder with threonine and uneven amination. In the grafting step, the grafting is incomplete, and the structure of the obtained granite powder-coated basalt fiber is unstable. In addition, the auxiliary agent is replaced by graphite in Comparative Example 2, which is unevenly mixed with other ingredients and has poor reinforcement properties, and cannot fully exert its corrosion resistance, high temperature resistance and water seepage resistance, which leads to poor overall performance of the concrete.
[0142] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0143] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing refractory concrete, characterized in that: The preparation method comprises the steps of modified basalt fiber, modified granite powder, grafting and mixing; The modified basalt fiber includes pretreatment and carboxylation steps; The pretreatment step comprises placing the basalt fiber in a plasma device for plasma treatment, controlling the vacuum degree to be 2.8-3.2 Pa, the treatment temperature to be 166-173° C., the treatment time to be 6.3-6.7 min, and the treatment power to be 324-332 W. After the treatment, placing the fiber in an ethanol solution, adding polyethylene glycol stearate and polyethylene glycol monolaurate, heating the fiber to 53-60° C. at a rate of 0.6-1.0° C. / min, stirring the fiber for 28-32 min, filtering and drying the fiber, and obtaining the pretreated basalt fiber. The carboxylation step comprises placing the pretreated basalt fiber in an ethanol solution, stirring evenly, adding a carboxylating agent for ultrasonic treatment, wherein the ultrasonic time is 18-23 minutes, the ultrasonic power is 110-120 W, the ultrasonic frequency is 23-28 kHz, and the ultrasonic temperature is 40-44° C. After the ultrasonic treatment, precooling treatment is performed, wherein the precooling time is 9.8-10.3 hours, and the precooling temperature is -26 to -22° C. After the precooling, freezing treatment is performed, wherein the freezing time is 22-24 hours, and the freezing temperature is -43 to -36° C. After the freezing, the modified basalt fiber is obtained; The carboxylating agent is a mixture of citric acid and salicylic acid; The step of modifying the granite powder is to place the granite powder in an ethanol solution, add sorbitol dodecanoate and polyoxyethylene sorbitan monolaurate and stir at a stirring temperature of 46-50° C., add threonine after stirring evenly, and perform ball milling treatment at a ball milling time of 26-30 minutes, a ball milling speed of 114-125 rpm, a ball-to-material ratio of 3-5:1, and after the ball milling is completed, filter and dry to obtain the modified granite powder; The grafting step is to add modified basalt fiber to N,N-dimethylformamide, add N,N-carbonyldiimidazole after stirring, introduce nitrogen, heat to 56-60°C, stir and react for 3.0-3.5h, add modified granite powder after the stirring reaction, heat to 85-88°C at a rate of 1.8-2.2°C / min, stir and react again, the reaction time is 7.8-8.3h, wash and dry after the reaction, and obtain granite powder coated basalt fiber; The mixing step is to add granite crushed stone, P.O42.5 ordinary Portland cement, fly ash, granite powder coated basalt fiber, and calcium carbonate whisker into deionized water, stir at a stirring speed of 435-461 rpm, add polycarboxylic acid water reducer, additive, polyoxyethylene alkyl alcohol amine, and carboxymethyl cellulose and continue stirring at a stirring temperature of 83-87° C., stir evenly, and cool to room temperature to obtain refractory concrete; The preparation method of the auxiliary agent is as follows: placing graphite in a 28-32wt% ethanol solution, heating to 53-57°C at a rate of 1.3-1.7°C / min, adding glycerol and paraffin, stirring evenly, adding gelatin for homogenization, the homogenization time is 4-6min, the homogenization pressure is 3.0-3.4MPa, and after the homogenization is completed, drying to obtain the auxiliary agent; The particle size of the graphite is 95-110nm; The mass ratio of the graphite, ethanol solution, glycerol, paraffin and gelatin is 11-13:45-50:0.6-0.8:1.3-1.5:1.1-1.
3.
2. The method for preparing refractory concrete according to claim 1, characterized in that: In the pretreatment step, the basalt fiber has a length of 1.0-1.4 mm and a diameter of 3.8-4.2 μm. The mass concentration of the ethanol solution is 33-37%, The mass ratio of the basalt fiber, the ethanol solution, the polyethylene glycol stearate and the polyethylene glycol monolaurate is 9.5-10.4:85-90:1.0-1.4:0.8-1.
2.
3. The method for preparing refractory concrete according to claim 1, characterized in that: In the carboxylation step, the mass concentration of the ethanol solution is 34-36%, The mass ratio of the pretreated basalt fiber, ethanol solution and carboxylating agent is 7.4-8.0:90-96:1.4-1.
7. In the carboxylating agent, the mass ratio of citric acid to salicylic acid is 1.1-1.3:1.4-1.
6.
4. The method for preparing refractory concrete according to claim 1, characterized in that: In the step of modifying the granite powder, the particle size of the granite powder is 135-145 nm. The mass concentration of the ethanol solution is 45-50%, The mass ratio of the granite powder, ethanol solution, sorbitan laurate, polyoxyethylene sorbitan monolaurate and threonine is 8.3-8.7:90-97:1.0-1.2:1.1-1.5:4.5-4.
9.
5. The method for preparing refractory concrete according to claim 1, characterized in that: In the grafting step, the mass ratio of the N,N-dimethylformamide, modified basalt fiber, N,N-carbonyldiimidazole, and modified granite powder is 1760-1830:4.1-4.4:0.16-0.2:10.3-10.
6.
6. The method for preparing refractory concrete according to claim 1, characterized in that: The particle size of the granite crushed stone is 5.2-5.6 mm, and the bulk density is 1710-1716 kg / m 3 ; The fly ash has a loss on ignition of ≤3.0%, a 45 μm sieve residue of ≤12%, and a moisture content of ≤1.0%; The mass ratio of the deionized water, granite crushed stone, P.O42.5 ordinary Portland cement, fly ash, granite powder coated basalt fiber, calcium carbonate whisker, polycarboxylic acid water reducer, additive, polyoxyethylene alkyl acylamine and carboxymethyl cellulose is 16-18:93-97:46-50:68-73:35-38:10-13:2.0-2.4:7.3-7.5:2.4-2.6:1.7-2.
0.
7. Refractory concrete obtained according to the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Fiber composite concrete with high fire resistance and method for preparing fiber composite concrete
CN109665782A
Glass fiber reinforced nylon composite material and preparation process and applications
BE1027292A1
Preparation method of coated impregnating compound for high-strength bonding basalt
CN108658480A